Caracterización cariotípica en mitosis y meiosis del robalo blanco Centropomus undecimalis(Pisces: Centropomidae) - Arias-Rodriguez, Lenin (2011)
The common snook Centropomus undecimalis inhabits marine, brackish and freshwater habitats in the Western Central Atlantic Ocean, including the Gulf of Mexico. Common snook is an economically important fish in many localities, nevertheless the number of studies on its biology and genetics are still few. The present study attempts to establish the cytogenetic profiles of the specimens collected in Paraiso Municipality Tabasco, Mexico. Tissue of five females and eight male organisms were processed by conventional cytological techniques to obtain chromosome slides of high quality in order to assemble the karyotype. The results from the kidney tissue analysis showed that 85.1% of 288 mitosis had a 2n=48 chromosomes, and 52.8% of 104 meiosis exhibited the haploid number 1n=24. The diploid karyotype showed 48 monoarmed chromo-somes of the telocentric (T) type. There was no chromosome heteromorphism between females and males. The diploid karyotype was very similar to that observed in the majority of marine fishes.